Strategic experimentation - Nicholls-Nixon, Charlene L; Cooper, Arnold C; Woo, Carolyn Y (Journal of Business Venturing, 2000)
This research was motivated by an interest in understanding more about the extent to which entrepreneurs initiate changes along various dimensions of strategy, the nature of those changes and their implications for firm performance. Our interest in this topic began with the observation that, within the large body of strategic-change literature, the research effort has focused almost exclusively on large and established firms. Moreover, a fundamental assumption underlying much of this work is that strategic change involves movement from one dominant strategic approach to another. This premise does little to motivate or contribute to the understanding of change and strategy in new ventures, where it is less likely that a dominant approach exists. Thus, we drew upon the literature in managerial cognition to develop the idea of strategic experimentation as the conceptual foundation for studying change and strategy in new ventures. Our basic premise is that in new ventures, changes along dimensions of strategy are reflective of a process of trial and error learning, whereby the entrepreneur seeks to develop an understanding of the competitive situation and determine how to compete within that context. Further, we suggest that some aspects of the firm's strategy are more likely to be the focus of experimentation than others. Building on these premises we developed a series of research hypotheses which propose that the greater the level of perceived environmental hostility, the higher the level of strategic experimentation that will be undertaken. We also propose that experimentation will always be greater along some dimensions of strategy than others, and that the degree of environmental hostility will influence the extent to which there are performance benefits associated with strategic experimentation. Our hypotheses are tested using data from a three-year study of over 400 young businesses. Overall, we find support for our assertions. For entrepreneurs and their advisors, this study has several important implications. First, it suggests that strategic experimentation is a normal part of the process by which entrepreneurs seek to position their businesses. Although the present study does not empirically address the linkage between formal planning and experimentation, the learning and cognition literature upon which the construct of strategic experimentation is based suggests that, no matter how much attention to detail is involved in the preparation of the business plan, the actual formation and development of the business will involve considerable adjustment to and/or deviation from that plan. This is because the process of new business development involves iterative changes in the way the entrepreneur positions his/her firm as he/she develops an understanding about what does and does not work. The results of this study further suggest that some dimensions of the firm's strategy are more likely to change than others. Specifically, it appears that peripheral changes (competitive emphasis and time allocation) are more likely to be the focus of such learning and adaptation efforts than core features (product scope and partnership status). This, in part, is because the former dimensions are easier to change than the latter. Moreover, our results show that ventures in more hostile environments clearly face difficult dilemmas. Although poor performance may stimulate experimentation along various dimensions of strategy, the complexity of learning within a hostile environment suggests that entrepreneurs will have a particularly difficult time determining the type of changes that will make a difference.